Temporal changes in stored-product insect populations associated with boot, pit, and load-out areas of grain elevators and feed mills. (September 2017) - Tilley, Dennis R.; Casada, Mark E.; Subramanyam, Bhadriraju; Arthur, Frank H.
Abstract: Commercial grain elevator and feed mill facilities can quickly become infested with stored-product insect pests, compromising the protection of the stored raw and processed cereal products. Elevators and feed mills were sampled monthly for adult stored-product insects in grain residues from the boot-pit areas and in bulk load-out samples from 2009 to 2010. The grain samples collected from the boot, pit, and load-out areas consisted of corn, soybeans, or a mixture of the two grains. Low insect densities were found in the boot-pit area during the cool winter months. Insect numbers increased in the spring and peaked during the warm summer months, prior to declining in the fall following a pattern of higher insect densities during higher ambient temperatures. The rice weevil, Sitophilus oryzae (L.), was the most prevalent species collected in all of the sampled grain residues, representing 69.2 and 35.8% of total insects collected in feed mills and elevators, respectively, during 2009 and was also commonly collected in 2010. Other commonly collected insect species included, the red flour beetle, Tribolium castaneum (Herbst); rusty grain beetle, Cryptolestes ferrugineus (Stephens); and sawtoothed grain beetle, Oryzaephilus surinamensis (Linnaeus). Our results showed that failing to clean out boot residual grain and a lack of sanitation of the pit area resulted in high numbers of insects that were transferred through the elevator leg to other locations within a facility. We conclude that the lack of sanitation at elevator and feed mill facilities allowed high numbers of insects to develop.